2019
DOI: 10.1002/nau.23963
|View full text |Cite
|
Sign up to set email alerts
|

Can we replace the catheter when evaluating urinary residuals?

Abstract: Aims To test the different formulae to calculate the bladder volume using ultrasound; the accuracy of patients hearing/feeling “bubbles” at the end of urodynamics testing as a measure of being empty; and how good we are at estimating PVR using X‐ray at the end of video urodynamics testing. Methods This was a prospective cohort study. Using Sonosite 180 plus, bladder volumes were calculated as, height × width × depth × proportionality constant (0.52, 0.625, 0.65, and 0.7) Patients were asked whether the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thus, our study reported a formula described in the human medical literature as being most accurate. 16 When compared to 2 previously reported formulas from the veterinary medical literature, the formula L × W × H × 0.52 resulted in less discrepancy between actual and infused UBV. Because the purpose of our study was to determine how UBV as measured by 3D ultrasound compared to the gold standard of 2D ultrasound measurements, and not that 3D ultrasound was superior to 2D ultrasound, we elected to use the most accurate 2D linear ultrasonographic measurement.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, our study reported a formula described in the human medical literature as being most accurate. 16 When compared to 2 previously reported formulas from the veterinary medical literature, the formula L × W × H × 0.52 resulted in less discrepancy between actual and infused UBV. Because the purpose of our study was to determine how UBV as measured by 3D ultrasound compared to the gold standard of 2D ultrasound measurements, and not that 3D ultrasound was superior to 2D ultrasound, we elected to use the most accurate 2D linear ultrasonographic measurement.…”
Section: Discussionmentioning
confidence: 86%
“…The formula L × W × H × 0.52 was used to calculate UBV based on a previously published study in people that reported high accuracy. 16 The formulas L × W × H × 0.2π and L × W × ([DL + DT]/2) × 0.625 (DL is depth on longitudinal ultrasound; DT is depth on transverse ultrasound) also were calculated based on previous veterinary studies. 2,15 The specified bladder volume subsequently was estimated using the 3D Verathon BladderScan Prime Plus by small animal internal medicine residents according to manufacturer instructions.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation